(untitled) (Journal of Medicine, 2025)
Takayasu’s arteritis is a rare, idiopathic large vessel vasculitis that affects large arteries, mainly the aorta and its branches.The coronary, pulmonary and renal arteries are also affected in the progression of the disease. We report a rare case of dilated cardiomyopathy in a 42 years old woman who was later diagnosed to have Takayasu’s arteritis using magnetic resonance angiography (MRA). She was subsequently treated by immunosuppressant therapy with prednisolone and methotrexate along with symptomatic treatment with gradual improvement of ventricular systolic dysfunction. Dilated cardiomyopathy (DCM) is reported to be seen in only 5-6% of cases of Takayasu’s arteritis. In a case of dilated cardiomyopathy screening for systemic vasculitis should be done if evidence of peripheral vascular disease is present, as timely initiation of immunosuppressant therapy can help in symptom-free survival. J MEDICINE 2025; 26(2): 156-159